Learning democracy in school and society education, lifelong learning, and the politics of citizenship - Biesta, Gert J. J. (SensePublishers, 2011)
This book explores the relationships between education, lifelong learning and democratic citizenship. It emphasises the importance of the democratic quality of the processes and practices that make up the everyday lives of children, young people and adults for their ongoing formation as democratic citizens. The book combines theoretical and historical work with critical analysis of policies and wider developments in the field of citizenship education and civic learning. The book urges educators, educationalists, policy makers and politicians to move beyond an exclusive focus on the teaching of citizenship towards an outlook that acknowledges the ongoing processes and practices of civic learning in school and society. This is not only important in order to understand the complexities of such learning. It can also help to formulate more realistic expectations about what schools and other educational institutions can contribute to the promotion of democratic citizenship. The book is particularly suited for students, researchers and policy makers who have an interest in citizenship education, civic learning and the relationships between education, lifelong learning and democratic citizenship. Gert Biesta (www.gertbiesta.com)is Professor of Education at the School of Education, University of Stirling, UK. - Publisher's description.